2018
DOI: 10.1101/342477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptional analysis reveals naïve helper ILC-like cells in zebrafish

Abstract: Innate lymphoid cells (ILCs) are important mediators of the immune response and homeostasis in barrier tissues of mammals. However, the existence and function of ILCs in other vertebrates is poorly understood. Here, we use single-cell RNA sequencing to generate a comprehensive atlas of zebrafish lymphocytes during tissue homeostasis and following immune challenge. We profiled 14,080 individual cells from the gut of wild-type zebrafish, as well as of rag1-deficient fish which lack T and B cells, and discovered … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…However, we also provide new evidence that mpeg1.1 + cells harness a transcriptional profile of NKL cells. The presence of NK and NKL cells in zebrafish has been determined by the identification of orthologs of mammalian NK-specific genes, namely novel immunetype receptors and NK lysins, by single-cell sequencing and morphological studies (22,23,51,52). However, functional studies of these cells have not yet been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also provide new evidence that mpeg1.1 + cells harness a transcriptional profile of NKL cells. The presence of NK and NKL cells in zebrafish has been determined by the identification of orthologs of mammalian NK-specific genes, namely novel immunetype receptors and NK lysins, by single-cell sequencing and morphological studies (22,23,51,52). However, functional studies of these cells have not yet been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the discovery that zebrafish hematopoiesis is strikingly similar to that of mammalian systems (20)(21)(22)(23)(24), including the establishment of a sophisticated adaptive immune system by 3 wk postfertilization, has opened up new avenues of investigation in adult zebrafish (21,25). The recent characterization of zebrafish T lymphocytes (26), B lymphocytes (20,27), and innate lymphoid cells such as NK cells (23) has demonstrated that the function and organization of immune cell populations share many similarities to their mammalian counterparts. Combined with their regenerative capacity, the adult zebrafish therefore provides a unique model system to characterize the complex inflammatory processes that govern natural regeneration in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…ILC populations were found that expressed the signature transcription factors T‐bet, RORγt, or GATA‐3. They were present in rag1 −/− fish and showed no signs of recombination at the TCR or BCR gene locus . ILC were also present, although in smaller numbers, in wildtype fish.…”
Section: Evolutionary Aspects and Outlookmentioning
confidence: 96%
“…While mammalian ILCs are mainly activated by cytokines, zebrafish ILCs express low levels of cytokine receptors and express high levels of “novel immune‐type receptors” (NITR), considered functional orthologs of mammalian NK receptors (NKR). Nitr9, one of the few activating NITR, is exclusively expressed by the “bi‐potent” ILC2/3 population . Finally, scRNA‐seq revealed an ILC population that could be an LTi ancestor because of the co‐expression of LTα ( tnfb ) and rorc .…”
Section: Evolutionary Aspects and Outlookmentioning
confidence: 99%
See 1 more Smart Citation